Effect of Drug Therapy on Net Cholesterol Efflux Capacity of High‐Density Lipoprotein–Enriched Serum in Rheumatoid Arthritis. Issue 9 (September 2016) - Ormseth, Michelle J.; Yancey, Patricia G.; Solus, Joseph F.; Louis Bridges, S.; Curtis, Jeffrey R.; Linton, MacRae F.; Fazio, Sergio; Davies, Sean S.; Roberts, L. Jackson; Vickers, Kasey C.; Kon, Valentina; Michael Stein, C.; et al.
Abstract : Objective: Patients with rheumatoid arthritis (RA) have an increased risk of coronary heart disease (CHD). Some RA therapies may modify this risk, but the underlying mechanisms are unclear. The cholesterol efflux capacity of high‐density lipoprotein (HDL) is associated with a reduced CHD risk in non‐RA populations; however, inflammation may impair the function of HDL. The aim of this study was to evaluate whether reduced inflammation resulting from treatment with methotrexate (MTX), adalimumab (ADA), or tocilizumab (TCZ) would increase the net cholesterol efflux capacity of HDL in patients with RA. Methods: A longitudinal multicenter study repository (Treatment Efficacy and Toxicity in Rheumatoid Arthritis Database and Repository) provided clinical information for and serum samples from 70 patients with RA before and 6 months after starting treatment with a new drug (MTX [n = 23], ADA [n = 22], or TCZ [n = 25]). Disease activity was measured using the Disease Activity Score in 28 joints using the erythrocyte sedimentation rate (DAS28‐ESR). The net cholesterol efflux capacity was measured in paired serum samples using THP‐1 macrophages, and total cellular cholesterol was measured by fluorometric assay. Results: The DAS28‐ESR decreased with all treatments ( P  < 0.001). Net cholesterol efflux capacity was not significantly changed after 6 months of new RA therapy (mean ± SD 36.9 ± 17.3% units at baseline versus 38.0% ± 16.9% units at 6 months [ P  = 0.58]). However, change in net cholesterol efflux capacity was associated with change in the DAS28‐ESR (ρ = −0.25, P  = 0.04). In a post hoc analysis of patients with impaired net cholesterol efflux capacity at baseline, treatment with TCZ resulted in significant improvement in net cholesterol efflux capacity (21.9 ± 14.7% units at baseline versus 31.3% ± 12.8% units at 6 months [ P  < 0.02]), but this was not observed with MTX or ADA. Conclusion: Net cholesterol efflux capacity of HDL cholesterol did not change significantly after 6 months of new RA therapy, except in patients with impaired baseline cholesterol efflux capacity who were receiving TCZ. Change in disease activity was associated with change in the net cholesterol efflux capacity.